DETERIORATION OF RENAL FUNCTION WITH INCREASED MORTALITY IN PATIENTS WITH HEART FAILURE (HF) - Basher Kareem Mohammed; Fadhil Faidhalla Mohialdeen; Mohaned Adel Jayan (Scholar Express Journals, 2022)
This study was conducted on patients who suffer from deterioration in kidney function, and this has another effect on heart failure. Information about patients such as age and gender was collected, in addition to the general characteristics of patients. The results are presented as a mean (M) and a mean (SD) standard deviation. To compare the quantitative indicators of two independent groups with the normal distribution of the trait, Student (t-test) was used. Differences were considered significant at P < 0.05. It was found that there were four stages between time one and time 2, stage 2 was kidney damage and a slight decrease in GFR 60 to 89 ml/min and stage 3 moderate decrease in GFR 30 to 59 ml/min as for stage 4 severe decrease in glomerular filtration rate from 15 to 29 ml/min and stage 5 stable renal failure less than 15 ml/min or when hemodialysis, statistically significant differences between the two stages were found greater or equal to 0.05 and FGe>60 ml/min was found at time 2 for patients While it was not found at the beginning of the study Through the results, we conclude that there is a positive relationship between the parameters (deterioration of renal function and mortality in patients with heart failure), and this study is our findings support the hypothesis that renal impairment could be a marker for worsening HF.
Keywords: FGe; CKD; HF; Renal Failure